CCGrid 2005. IEEE International Symposium on Cluster Computing and the Grid, 2005. 2005
DOI: 10.1109/ccgrid.2005.1558655
|View full text |Cite
|
Sign up to set email alerts
|

Execution time prediction in DSM-based mobile grids

Abstract: Mobile Grids are collaborative, resource sharing environments formed by a collection of heterogeneous devices ranging from fixed PCs to wireless devices such as PDAs, laptops, cellulars etc. We investigate the Distributed Shared Memory (DSM) paradigm in the context of Mobile Grid computing. The uncoupled communication paradigm provided by DSM systems is well desirable in a mobile environment because it provides means for handling the temporary unavailability of resources. We tackle the problems of mobile (disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Finally, we compared the MRRJSM with the RTJSM [10] and the ETPJSM [11], which are job scheduling models for mobile grid, in Section 4.3. In result, we confirmed that the MRRJSM provides more improved computing performance than the RTJSM and the ETPJSM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we compared the MRRJSM with the RTJSM [10] and the ETPJSM [11], which are job scheduling models for mobile grid, in Section 4.3. In result, we confirmed that the MRRJSM provides more improved computing performance than the RTJSM and the ETPJSM.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, a scheduler obtains the response time of all mobile resources and allocates a job to a mobile resource with the fastest response time. M. Ballette, A. Liotta, and S. M. Ramzy proposed the execution time prediction model for job scheduling in a mobile grid environment [11]. The execution time of a mobile resource is the sum of its processing time and data transmission time, which is effected by its predicted disconnectivity.…”
Section: Grid Schedulingmentioning
confidence: 99%
See 1 more Smart Citation